Perceptions of employer branding dimensions and its effects on employee’s intention to stay - Peixoto, Mariana de Freitas (2021)
What makes an organisation attractive? What elements define it? The current challenge for organisations is to understand which features can promote a positive perception among employees and potential employees. Employer branding is increasingly getting attention among practitioners. Although the concept converges on attracting and retaining talent, there are few studies regarding employees' perception on employer branding. In this sense, the aim of this dissertation is to analyse which perceived employer branding dimensions have influence in Portuguese employee’s retention, in the Information and Communication Technologies sector. The methodology adopted was the quantitative approach through the application of an online questionnaire. The two main variables of the study were related to employer branding and employee retention. Thus, two instruments were used to analyse it: Employer Branding Measurement Scale developed by Tanwar and Prasad (2017), and part of the proposal in Bussin and Mouton (2019) research. Findings revealed that the dimensions of employer branding have influence on employee retention. These results contribute to the existent literature on employer branding and its effects on talent retention, as well as assist organisations to acknowledge what elements should be considered when developing its employer brand.